Analisis Persepsi Siswa Madrasah Al Hidayah terhadap Pelatihan Public Speaking dalam Meningkatkan Kepercayaan - Moh.Syifauddin; Muhammad Syaiful Rizal; Rizqilla Syahri Ramadhany; Muhammad Arif Rizqy Fachrudin; Revalina Kawindra (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze students’ perceptions of public speaking training in improving self-confidence at Madrasah Al Hidayah Betoyokauman. The research is motivated by the low level of students’ self-confidence when speaking in public, which is often characterized by nervousness, fear, and reluctance to express opinions. This study employed a qualitative descriptive approach to explore students’ subjective experiences and interpretations after participating in public speaking training. The research activities were conducted on Thursday, January 8, 2026, through material presentations and direct public speaking practice, including roles such as master of ceremony, presentations, speeches, and stand-up comedy. Data were collected using a student perception questionnaire to capture students’ views and experiences regarding changes in self-confidence after the training. The results indicate that students generally have positive perceptions of the public speaking training and experience an improvement in self-confidence, as reflected in increased speaking courage, better control of nervousness, and stronger belief in their own abilities. The training not only enhances students’ speaking skills but also serves as a medium for developing students’ soft skills. This study implies that public speaking training can be implemented as a supportive program to improve students’ self-confidence and communication skills in the madrasah environment.